1997
DOI: 10.1007/bf02778195
|View full text |Cite
|
Sign up to set email alerts
|

Oral aluminum administration and oxidative injury

Abstract: For a long time, aluminium (Al) has been considered an indifferent element from a toxicological point of view. In recent years, however, Al has been implicated in the pathogenesis of several clinical disorders, such as dialysis dementia, the fulminant neurological disorder that can develop in patients on renal dialysis. In the present study, the effect of chronic oral administration of Al on certain biochemical parameters of brain homogenate has been investigated. The feeding of test diet for 6 wk resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 13 publications
7
20
2
Order By: Relevance
“…In the present experiment, there was a significant increase in lipid peroxidation following AlCl 3 exposure, determined by TBARS and HP levels in rat testes. Our result are in agreement with many authors who have reported a significant increase in TBARS and HP in the kidney, liver and brain of rats exposed to aluminum salts [41,[49][50][51] . Also, our findings correlate with those published by Yousef et al [25] who demonstrated that, in rabbits orally treated with AlCl 3 , there was a significant increase in the level of TBARS in the seminal plasma.…”
Section: Discussionsupporting
confidence: 94%
“…In the present experiment, there was a significant increase in lipid peroxidation following AlCl 3 exposure, determined by TBARS and HP levels in rat testes. Our result are in agreement with many authors who have reported a significant increase in TBARS and HP in the kidney, liver and brain of rats exposed to aluminum salts [41,[49][50][51] . Also, our findings correlate with those published by Yousef et al [25] who demonstrated that, in rabbits orally treated with AlCl 3 , there was a significant increase in the level of TBARS in the seminal plasma.…”
Section: Discussionsupporting
confidence: 94%
“…In the present report, we observed a significant increase in lipid peroxidation after AlCl 3 exposure, as measured in terms of TBARS and HP levels in the liver and kidney of the rats. These result are in agreement with many studies that also demonstrated a significant increase in TBARS and HP in the kidney, liver and the brain of rats after intoxication by aluminum salts [53,60,63,64] . The increased lipid peroxidation is due to inhibition or a change in the activity of non-enzymatic and enzymatic components of the oxidative system, i.e., GSH, SOD and CAT, in the liver and kidney.…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrated that oral administration of AlCl 3 caused a significant increase in serum cholesterol and triglycerides, which may indicate a loss of membrane integrity, disturbance of lipid metabolism and/or liver dysfunction [52] . With regards to renal damage, biochemical findings in this study are in agreement with other studies [11,14,47,53] demonstrating that the oral administration of AlCl 3 resulted in a significant increase in serum urea and creatinine and a substantial decrease in total protein and albumin levels compared to control animals. Collectively, these findings demonstrate that accumulation of aluminum in the kidneys may promote degeneration of renal tubular cells leading to nephrotoxicity [11,14] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with other authors that a signifi cant increase in TBARs in the liver and kidney after aluminum intoxication. 21,22 This elevation of LPO in the liver and kidney was evident by the increased production of TBARS, which suggests participation of free-radical induced oxidative cell injury in mediating the toxicity of Al. 21 Abubakar et al, ascertained that even small quantities of aluminum in hepatocytes associated with an increase in ROS and peroxidation.…”
Section: Discussionmentioning
confidence: 95%